Osteogenic Sarcoma in an Adolescent With Cystic Fibrosis: Successful Treatment Despite Significant Obstacles - Thomas J. C. Ruffles; Thomas J. C. Ruffles; Ryan Black; Ryan Black; Wayne Nicholls; Barbara Laing; Alan Isles; Alan Isles (Frontiers Media S.A., 2018)
Introduction: We describe the case of a 16-year old male with cystic fiborosis (CF) who presented with an osteosarcoma of his right distal tibia.Case Report: Treatment consisted of neoadjuvant chemotherapy of cisplatin, doxorubicin and high dose methotrexate followed by distal tibial resection and free fibula flap reconstruction and consolidation chemotherapy. Treatment was complicated by a pulmonary exacerbation, where Pseudomonas aeruginosa (PsA) and Staphylococcus aureus were grown on sputum culture which was treated with a 2-week course of intravenous piptazobactam and tobramycin. Mycobacterium intracellulare and Mycobacterium abscessus were also cultured following commencement of chemotherapy and successfully treated with a 6-month course of oral azithromycin, ethambutol, and moxifloxacin along with a 1-month course of inhaled amikacin. Pulmonary function improved during his treatment from baseline FEV1 of 3.8 l (93.9%) to 4.15 l (102.3% predicted) whilst nutritional status remained stable.Discussion: The combination of CF and osteosarcoma is rare with only one previous case reported (1). Our case is instructive as the patient faced the challenge of chronic PsA and the first reported culturing and successful treatment of non-tuberculous mycobacterium (NTM) during chemotherapy. Fatal outcomes have been reported previously for CF patients during immunosuppression (2). In concordance with our findings, a recent report noted an improvement in respiratory function in a child treated for leukemia (3). The anti-inflammatory nature of some chemotherapy agents could be responsible for the observed clinical improvement in CF with low dose methotrexate having been shown to increase FEV1 in adolescents with advanced CF (4). Whilst doxorubicin could improve pulmonary outcomes through increased total cellular CFTR protein expression and CFTR associated chloride secretion (5). It is hypothesized that the improved pulmonary function in patients with CF who require chemotherapy could be due to increased production of Multi-Drug Resistance Proteins (MDR) and Multi-Drug Resistant Associated Proteins (MRP) that may complement the depleted CFTR protein (6).Concluding Remarks: We report the well-tolerated management of osteosarcoma in a patient with CF including the first reported identification and eradication of NTM during chemotherapy. The observed positive pulmonary outcome following chemotherapy highlights several potential cellular mechanisms that deserve to be explored.